CHARACTERIZATION OF CHARACTERS IN SALAM SADIGZADEH’S NOVEL “THERE IS A BEAUTIFUL WOMAN IN OUR VILLAGE” - Гюнель Сафарова (KONFERENSIYALAR, 2025)
Abstract. One of Salam Sadigzadeh’s works, which has an interesting plot line, is distinguished by its sincere description of events, and talks about the spiritual and moral qualities of young people, is the novel "There is a beautiful woman in our village", which consists of 15 short stories. Although the novel has been discussed in various articles, it has not been studied in detail. From this perspective, the study of the novel is both relevant and interesting. The events that happen to a woman, their negative effects that have on her life, their negative marks left on her character, the betrayal of the wife to a husband who lost his eyes in the war, the killing of a mother the baby who thought she was his child, etc. issues are reflected in the novel.